Upaya Perlindungan Hukum Bagi Korban Tindak PidanaPerdagangan Anak Di Surakarta - Mareta, Friska Ardin; , Dr. Natangsa Surbakti, S.H., M.Hum (2017)
The purpose of this study to determine the legal rrangements and the factorsdriving the Crime of Trafficking in Children and their protection as well as theefforts made to order to the occurrence of child trafficking, especially inSurakarta. The research method using descriptive empirical jurisdiction. The datasource consists of the primary data and secondary data, interview the legal data ofprimary, secondary and tertiary. Data were collected through the study ofliterature and field research (interviews), then the data is analyzed qualitatively.The results showed legal arrangements on the Crime of Trafficking and itsprotection, including the Code of Penal (Penal Code), Act No. 21 of 2007 on theEradication of Trafficking in Persons, Act No. 35 of 2014 on amendment oF No.23 of 2002 on protection of hildren, as well as the special protection oftrafficking victims. The driving factors for the occurrence of, among thers,socially, curiosity, economic, family, environment, law enforcement andsupporting factors are the times, transport, technology and communications, thehigh demand for sex workers as well as lack of education and employmentopportunities, mobility of women and children is limited, and reduction of public concern. The efforts to overcome with religious education, children's needsfulfilled, and controlling of children.